Kebijakan Pengembangan dan Pembinaan Industri Kecil Modern pada Industri Pengolahan Pangan - Shafira, Alvinia; Aurellia, Azarine Faustina; Nurrizki, Diza; Wiratmadja, Iwan Inrawan (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2024)
In the context of industrial development, micro, small, and medium-sized enterprises (MSMEs) are considered flexible in capitalizing on business opportunities and are perceived as more resilient during economic crises. However, intensifying global competition underscores the importance of technology as a determinant of success. MSMEs need to enhance their technological capabilities to improve their business performance, despite frequently facing financial constraints. The government's role in supporting MSMEs becomes crucial through the development of infrastructure and policies that foster the growth of small industries, strengthen competitiveness, and facilitate product exports. The aim of this article is to formulate effective development policies for the technological components and operational policies to support the growth of X MSME. The methodology used involves a review of relevant literature on policies for modern small industries, encompassing small industry development approaches, problem-solving solutions, guiding principles for small industry development policies, the triple helix model, operational policies, continuous strategic improvement, and criteria for small industry development success. The article's findings recommend development policies based on Technoware, Humanware, Inforware, and Orgaware (THIO) aspects to be implemented by X MSME, along with operational policies from the government as a form of support and guidance for MSMEs.